In vitro fertilisation: past - present - future - Bompiani, Adriano; Garcea, Nicola (Medicina e Morale, 1986)
In vitro fertilisation is a clinical biological issue that has immediate ethical and legal implications. It is therefore not possible to deal with just one aspect, separating it from the others, and even the biologist, carrying out his role in the clinical field (in collaboration with the gynaecologist) is obliged to take an in-depth interest in ethical and legal issues, which is not always the case.